Whole Language Approach Implementation as a Child Language Learning Model Development - Nanda Saputra; Wiputra Cendana; Irnie Victorynie; Khaidir (Britain International for Academic Research (BIAR-Publisher), 2021)
This research was conducted to implement a holistic language approach (whole language approach) as a development model for students' language learning at SDN (Public School) 2 Sigli. This study uses a classroom action research method by providing action in each cycle starting from planning, acting, observing, and reflecting. This research was conducted at the Sigli 2 Public Elementary School. The subjects of this study consisted of 10 students consisting of 6 boys and 4 girls. The results of observations were processed through data analysis techniques with descriptive statistics, namely finding the percentage and average value of the improvement in Indonesian language skills obtained through observation, interviews and discussions, and document review. The results showed that the implementation of the whole language approach which includes immertion, demonstration, expectation, responsibility, employment, approximation, and feedback can improve students' reading ability. Based on the results of observations in the pre-cycle, the percentage of pre-cycle reading ability was still 30.25%. In the first cycle, after the action was carried out for 7 meetings, the percentage increased to 85.50%. Based on these data shows an increase in the percentage of reading ability from the results of pre-cycle observations by 55.25%. The implication of this research is that the whole language approach is expected to be used as the development of a language learning model at SDN 2 Sigli, because it is natural and fun and is the same age as the stages of student development.